Women acting for women: Gender-responsive budgeting in Timor-Leste - Costa, Monica; Sawer, M.; Sharp, R. (Routledge, 2013)
In the new country of Timor-Leste, women constituted in 2011 32 per cent of the parliament, a relatively high figure in the world and in the region. But to what extent has the presence of women in parliament contributed to progress towards gender equality? In this article we argue that the passage of a parliamentary resolution on gender-responsive budgeting in Timor-Leste was an act of substantive representation, and we draw on a range of data to examine what made it possible. We find that while newness, international norms, women's movement unity, women's machinery in government and parliament and networks linking them were important, it was the development of a cross-party parliamentary women's caucus that was crucial to success. The role of gender-focused parliamentary institutions in supporting critical actors has rarely been examined in the literature on substantive representation. This is in contrast to the rich literature on institutions such as women's policy agencies. Our study suggests that more focus on parliamentary institutions is needed to discover what enables women parliamentarians to become critical actors. © 2013 Copyright Taylor and Francis Group, LLC.